HUBUNGAN PERSEPSI DENGAN SIKAP MASYARAKAT TERHADAP PENCEGAHAN COVID-19 di KOTA MATARAM - Nabila Araishabeby Yudhyatirta; I Putu Dedy Arjita; Dany Karmila; Aena Mardiah (Nusantara Hasana Journal, 2023)
COVID-19 is an infectious disease caused by coronaviruses (CoV). Currently, COVID-19 is a pandemic throughout the world, including in Indonesia. Many efforts have been made to prevent contracting this covid-19. However, there are still many people, especially in the city of Mataram, who have not done it. Therefore, research is needed to find out how far the perceptions and attitudes of the community are in preventing covid-19. The purpose of this study was to determine the relationship between perceptions and public attitudes towards COVID-19 in Mataram City. This study is an observational analytic study with a cross sectional design. The research time was in December 2022 - January 2023. The research sample was obtained as many as 450 people. Data were analyzed by Chi-square test with a significance value / p-value <0.05. The results showed that the characteristics of the respondents were mostly female 78%, Sasak tribe 62.3%, secondary education 61.4%, Islamic religion 82.5%, not working 39.7%. The results of the univariate test showed that the majority of respondents had the right perception of 81.1% and an agreeable attitude of 79.2%, and the bivariate test obtained a p value = 0.000 (p < 0.05). There is a relationship between perceptions and community attitudes towards COVID-19 prevention.